Translation Techniques and The Impact used by Translation for Post On Facebook - Ika Oktaria Cahyaningrum; Widyashanti K. Anindita; Budi Purnomo; Nurul Intan Sari (Universitas Musamus Merauke, 2022)
This study focuses on the use of translation techniques used by one of the social media Facebook, which is one of the media that facilitates automatic translation into various languages, so that there are no more obstacles in communicating with anyone in the world. Translation for Post is one of the facilities provided by Facebook in translation. Even so, Translation for Post is also entered into machine translation, which in terms of translation quality has shortcomings and the resulting equivalence. Likewise with Translation for Post, so researchers are interested in analyzing the use of translation techniques used by Facebook. The object of this research is a post on social media facebook using descriptive qualitative research techniques, with purposive sampling method. The results obtained, the dominance of the use of literal translation techniques has an impact on the quality of the resulting translation. Often in machine translation, the use of literal translation techniques makes the quality of the resulting translation make the translation feel less and grateful. So the choice of technique will also determine the quality of the resulting translation.